2017
DOI: 10.3390/app7080796
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Ferulic Acid Production from Rice Bran Oil Soapstock Using a Homogenous System

Abstract: Ferulic acid (FA) is widely used as an antioxidant, e.g., as a Ultraviolet (UV) protectant in cosmetics and in various medical applications. It has been produced by the hydrolysis of γ-oryzanol found in rice bran oil soapstock. In this study, the base-catalyzed, homogenous hydrolysis of γ-oryzanol was conducted using various ratios of potassium hydroxide (KOH) to γ-oryzanol, initial concentrations of γ-oryzanol in the reaction mixture, and ratios of ethanol (EtOH) (as cosolvent)/ethyl acetate (EtOAc) (γ-oryzan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Esters of ferulic acid reduced the yield of catechol (2)w ith increasing chain length (methyl (8a), ethyl (8b), and propyl (8c)ester), linked to substrate solubility.C hlorogenic acid (9), involved in biosynthesis of lignin, [16] delivered 2 in 41 %y ield. Lacton esculetin (10), the main active ingredient of the traditional Chinese medicine Cortex Fraxini, [17] gave hydroxyquinol (7) with ay ield of 56 %. Other propenyl containing substrates, that is,coniferylalcohol (11), isoeugenol (12 a), eugenol (12 b), and ortho-eugenol (12 c), also cleaved with the formation of 2 in yields ranging from 42 to 65 %.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…Esters of ferulic acid reduced the yield of catechol (2)w ith increasing chain length (methyl (8a), ethyl (8b), and propyl (8c)ester), linked to substrate solubility.C hlorogenic acid (9), involved in biosynthesis of lignin, [16] delivered 2 in 41 %y ield. Lacton esculetin (10), the main active ingredient of the traditional Chinese medicine Cortex Fraxini, [17] gave hydroxyquinol (7) with ay ield of 56 %. Other propenyl containing substrates, that is,coniferylalcohol (11), isoeugenol (12 a), eugenol (12 b), and ortho-eugenol (12 c), also cleaved with the formation of 2 in yields ranging from 42 to 65 %.…”
Section: Zuschriftenmentioning
confidence: 99%
“…One particularly interesting biorenewable aromatic compound is ferulic acid (1a), found in plant cell walls covalently linked to (hemi)cellulose and lignin. [6] In most cases,i ti s obtained as aw aste compound of the rice industry,b y extraction from rice bran, [7] and therefore readily available on al arge scale.R ice bran derived 1a is used by Solvay to produce vanillin industrially ("Rhovanil Natural") by biocatalysis (fermentation). [8] Interestingly, 1a contains a4 -substituted catechol moiety as core structure.C atechol (2)i s amajor commodity chemical (40 kilotons year À1 )petrochemically mainly produced through hydroxylation of phenol, [5a,d] synthesized from benzene by the cumene Hock process.…”
mentioning
confidence: 99%
“…Panda et al () pointed out that sunflower oil soapstock can be used as an available energy source in the diet of broiler chicken. Meanwhile, soapstock is one of the most promising candidates for bioactive molecule extraction, such as ferulic acid (Truong et al, ), γ‐oryzanol (Narayan et al, ), and gossypol (Jia et al, ), and this economical practice will help relieve environmental pollution and resource waste to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, degumming and neutralization may decrease the contents of PAH and PAE in the soybean oils, whereas they increase their amounts in the soybean oil gums and soapstocks, reducing the safety when using them as starting materials to produce feeds and high value‐added products due to regulatory standards promulgated by countries and organizations all over the world concerning the concentrations of these harmful pollutants in food additives and other food‐related products (EFSA, ; European Commission, ). As gums and soapstocks are important by‐products that have been widely utilized in various fields (Escalera‐Valente et al, ; Pekel et al, ; Truong et al, ), the utilization of these types of wastes has given rise to certain concerns as some of them are food chain materials. However, based on our literature review, no study investigating their distributions in soybean oil gums and soapstocks has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…FA cannot be extracted directly from their matrix in the rice bran [14] because of existence of conjugated forms and/or its ester form of c-oryzanol. However, FA can be produced from c-oryzanol-containing by-products by hydrolysis reaction, for example, soapstock from rice bran oil processing [15,16].…”
Section: Introductionmentioning
confidence: 99%